The trial of a Nazi doctor : Franz Lucas as defendant, opportunist, and deceiver - Wisely, Andrew C. (2024)
"The trial of a Nazi doctor examines the life of Franz Bernhard Lucas (1911-1994), an SS camp doctor with assignments in Auschwitz, Mauthausen, Stutthof, Ravensbrück, and Sachsenhausen. Covering his career during the Third Reich and then his prosecution after 1945, especially in the Frankfurt Auschwitz trial, Andrew Wisely explores the lies, obfuscations, misrepresentation, and confusions that Lucas himself created to deny, distract from or excuse his participation in the Nazi's genocidal projects. By juxtaposing Lucas's own testimonies and those of a wide range of witnesses: former camp inmates and Holocaust survivors; friends, colleagues, and relatives; and media observers, Wisely provides a nuanced study of witness testimonies and the moral identity of Holocaust perpetrators